Archiving a Life's Work: An Interview with Ismail Khayat. (1st January 2018) - Khayat, Ismail; Abdullah, Meriwan
Abstract : Meriwan Abdullah interviews Kurdish artist Ismail Khayat about the importance of documenting the work of Kurdish artists and how art can express the stories and record the histories of the Kurdish people.